Morphological Criteria Bronchiectasis Disease (Eurasian Medical Research Periodical, 2023)
The article is devoted to the morphological criteria of bronchiectatic disease in children. The presence of morphological structures characterizing different manifestations of pathology in bronchiectatic disease has been established. At the same time the preservation of the bronchial epithelium structure provides the afferent phase of the immune response of the mucous membrane in inflammatory processes. In particular, the study showed that in inflammatory processes in the lungs associated with bronchiectatic disease, the interaction of immune and endocrine structures in the epithelium is noted